Association between body dissatisfaction and bullying in children of socioeconomically vulnerable areas. Issue 6 (November 2017) - Zequinão, Marcela Almeida; de Medeiros, Pâmella; do Rosário, Helena Rafaela Vieira; Pelegrini, Andreia; Lopes, Luis; Pereira, Beatriz; Cardoso, Fernando Luiz
ABSTRACT : Highlights : The association between body image, body composition and school bullying was evaluated. 409 children with 11.14 years in high social vulnerability in Brazil participated. Victim–aggressor bullying participants are dissatisfied with thinness. Girls aged 8–10 years and with high fat % have dissatisfaction with excess. Body dissatisfaction showed associations with body composition and bullying. Aim: : To analyze the association between dissatisfaction with body image and weight status and the roles assumed in school bullying in children and adolescents living in a socioeconomically vulnerable area. Method: : 409 children and adolescents with average age of 11 years, from Florianópolis, Brazil, participated in this study. The body image was self‐assessed through the Body Silhouettes Scale, the weight state through the body mass index (BMI) and the roles of participation in bullying through the Olweus Questionnaire. Results: : It was verified a significant association between "dissatisfaction with thinness" and (i) weight status, (ii) sex and (iii) roles of participation in bullying. In addition, low weight, boys and bully‐victims presented a greater odds of body dissatisfaction due to thinness. The variable "dissatisfaction with excess" was negatively associated with age and weight status. Participants aged 11–12 years and 13 and 16 years, as well as children and adolescents with low weight, had lower odds of having excessive dissatisfaction. Conclusion: : The associations found in this study are important tools for developing interventions to avoid or minimize the effects of early body dissatisfaction and consequently violence at school, especially in children with increased determinants such as those living in socioeconomically vulnerable areas.